Participatory Action Research - Vidallo, Rene R.; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Gonsalves, Julian Francis (2019)
The poster presents how farmers' participation in action research enhances their knowledge on climate-resilient agriculture.